Minimal Invasive Decompression for Lumbar Spinal Stenosis - Victor Popov; David G. Anderson (Advances in Orthopedics)
Lumbar spinal stenosis is a common condition in elderly patients and may lead to progressive back and leg pain, muscular weakness, sensory disturbance, and/or problems with ambulation. Multiple studies suggest that surgical decompression is an effective therapy for patients with symptomatic lumbar stenosis. Although traditional lumbar decompression is a time-honored procedure, minimally invasive procedures are now available which can achieve the goals of decompression with less bleeding, smaller incisions, and quicker patient recovery. This paper will review the technique of performing ipsilateral and bilateral decompressions using a tubular retractor system and microscope.